Characterization of Biochemical Cartilage Change After Anterior Cruciate Ligament Injury Using T1ρ Mapping Magnetic Resonance Imaging. Issue 5 (13th May 2015) - Osaki, Kanji; Okazaki, Ken; Takayama, Yukihisa; Matsubara, Hirokazu; Kuwashima, Umito; Murakami, Koji; Doi, Toshio; Matsuo, Yoshio; Honda, Hiroshi; Iwamoto, Yukihide
Background: Patients with anterior cruciate ligament (ACL)–injured knees are at an increased risk of posttraumatic osteoarthritis (OA). OA changes secondary to ACL injuries have many variations, and when and where early cartilage degenerative change begins has not yet been established. Purpose: To characterize the location of cartilage degeneration after ACL injury associated with time since injury using T1rho (T1ρ) mapping. Study Design: Cross-sectional study; Level of evidence, 3. Methods: In this study, 49 knees with ACL injuries and 14 normal knees from uninjured volunteers were imaged with a 3.0-T magnetic resonance scanner. Three regions of interest (ROIs) were defined in the cartilage at the weightbearing area of the femoral condyles (anterior, middle, and posterior zones). Two ROIs were defined in the tibial plateau (anterior and posterior zones). The T1ρ values within the ROIs were measured. Patients were allocated into 3 groups based on time since injury: <12 weeks (group A; 28 patients), 12 weeks to 2 years (group B; 14 patients), and >2 years to 5 years (group C; 7 patients). Results: Mean T1ρ values were significantly greater in the anterior and middle ROIs of the medial femoral condyle in group C compared with those in other groups ( P < .05). Patients with medial meniscus injury, for whom the time since injury was ≥12 weeks, exhibited significantly greater T1ρ values in the middle areas of the medial femoral condyle versus normal knees and ACL-injured knees without medial meniscus injury. Conclusion: The risk of cartilage degeneration in the area of the femoral condyle that contacts the tibia during small degrees of flexion increased when the time since injury was longer than 2 years. In addition, medial meniscus injury was associated with cartilage degeneration at the medial femoral condyle in the chronic phase. Clinical Relevance: Cartilage degeneration occurs more than 2 years after ACL injury and increases with medial meniscus injury. Early intervention may be desirable for meniscus injury.